2023
DOI: 10.3390/healthcare11070933
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trends in Sociodemographic Disparities and COVID-19 Morbidity and Mortality—A Nationwide Study during Two Years of a Pandemic

Abstract: Social epidemiological research has documented that health outcomes, such as the risk of becoming diseased or dying, are closely tied to socioeconomic status. The aim of the current study was to investigate the impact of socioeconomic status on morbidity, hospitalization, and mortality outcomes throughout five waves of the pandemic amongst the Israeli population. A retrospective archive study was conducted in Israel from March 2020 to February 2022 in which data were obtained from the Israeli Ministry of Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several risk factors have been recognized to affect COVID-19 infection, such as socioeconomic, anthropometric, and lifestyle factors [10]. Several studies have demonstrated that health outcomes like the probability of developing a disease and then dying are highly associated with the socioeconomical state [11]. Studying viral pulmonary disorders and the 1918, 1919, and 2009 influenza pandemics had previously highlighted a higher likelihood of contracting the disorder and dying among socioeconomically disadvantaged people [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have been recognized to affect COVID-19 infection, such as socioeconomic, anthropometric, and lifestyle factors [10]. Several studies have demonstrated that health outcomes like the probability of developing a disease and then dying are highly associated with the socioeconomical state [11]. Studying viral pulmonary disorders and the 1918, 1919, and 2009 influenza pandemics had previously highlighted a higher likelihood of contracting the disorder and dying among socioeconomically disadvantaged people [12,13].…”
Section: Introductionmentioning
confidence: 99%